GREEN INNOVATION, SUSTAINABLE COMPETITIVE ADVANTAGE DAN SUSTAINABILITY PERFORMANCE - Marpaung, Elyzabet Indrawati; Setiana, Sinta; Wijaya, Anggela - (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
ABSTRACT Today companies must be environmentally responsible to contribute to social welfare and achieve levels of competitiveness and financial success.This research aims to test whether green innovation has an effect on sustainable competitive advantage, whether sustainable competitive advantage has an effect on sustainability performance, whether green innovation has an effect on sustainability performance, and whether sustainable competitive advantage can mediate the effect of green innovation on sustainability performance. This research uses research methods with quantitative design and survey methods. Respondents in this research were employees of companies in Indonesia in the raw goods, industrial, primary consumer goods, non-primary consumer goods and health sectors who had work experience of more than 3 years. Data were analyzed using Structural Equation Modeling (SEM) with the alternative partial least squares method as a tool to help draw conclusions. The research results show that green innovation has a positive effect on sustainable competitive advantage, sustainable competitive advantage and green innovation have a positive effect on sustainability performance, and sustainable competitive advantage can mediate the effect of green innovation on sustainability performance, so it can be concluded that the type of mediation in this research is partial mediation.Keywords: Green Innovation, Sustainable Competitive Advantage, Sustainability Performance